PERKEMBANGAN FISIK KOTA MADIUN TAHUN 1998-2008 - , Emri Widyantari, S.Pd., Prof. Dr. Hadi Sabari Yunus, MA, DRS ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Changes in land use have provided impacts on urban development. The changes in the shape and the acreage of land use in the certain period of time have affected the spatial pattern of Madiun City. This research aimed to: (1) study the spatial distribution of physical development of Madiun City, (2) study the factors and determinants affecting physical development in Madiun City, and (3) analyze the development trend of Madiun City. This was a survey research with data collected using questionnaires based on the purposive sampling technique, i.e. samples were taken based on particular objectives. This research involved three stages, namely: laboratory activities, field studies and data analysis. Data processing method were spatial analysis, quantitative analysis, and qualitative analysis with spatial approach. The results of this research showed that (1) the spatial distribution of Madiun City produced changes in shape and acreage of land use, including the greatest change in the area of land, from rice fields into settlement areas of 208.43 hectares (48.58%), and also the increase in number and distribution of physical facilities during the last 10 years